Efecto teratogeno de la aflatoxina B1 sobre embriones murinos - Cabrera, P.=700 1 Fernandez, A.; Diaz, T.; Bastidas, P.; Molina, M.; Bethencourt, A.; Ascanio, E.
(En, Es)
ilus., 6 ref.
Keywords: ROEDORES; ETAPAS DE DESARROLLO ANIMAL; EMBRIONES ANIMALES; AFLATOXINAS; ALIMENTO; VENEZUELA; MURINOS; AGRONOMIA TROPICAL